Clinico-Pathological Analysis of Thymic Epithelial Tumours: An Institutional Study - S, Divya; Raju, Sreeja; Augustine, Joy; Kumar, Ajay (Annals of Pathology and Laboratory Medicine, 2018)
Background: Thymic epithelial tumours are anterior mediastinal neoplasms and they exhibit a spectrum of histomorphological features. Methods: In this study we analysed the clinico-pathological spectrum of thymic epithelial tumors at our institution. It is a retrospective and descriptive study done at our Department of Pathology, Amala Institute of Medical Sciences, Thrissur, Kerala over a period of ten years from August 2008 to August 2018. Histological sections of each case were meticulously analysed. Immunohistochemistry was done if needed. Result: In this study 17 cases of thymic epithelial tumors were analysed. A male preponderance of 58.8% was observed. Age ranged from 24 to 73 years with a mean age range of 54.4 years. Most common histological subtype of thymoma was Type B and Type AB. 4 cases were associated with myasthenia gravis. Masaoka Stage I was commonly observed. Conclusion: Thymic epithelial tumors are a unique group of anterior mediastinal neoplasms which also pose a diagnostic challenge. This study highlights the significance of clinico-pathological correlation and staging of thymic neoplasms.